2021
DOI: 10.1096/fasebj.2021.35.s1.00192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibration Training on Bone Mineral Density: A Systematic Literature Review

Abstract: Purpose Whole body vibration (WBV) training is purported to improve bone mineral density. Numerous randomized controlled trials present unclear data as to its clinical significance. This systematic literature review aims to collect the general consensus of data on the topic. Data Sources Systematic literature searches for randomized controlled trials between 2015‐2020 were performed in the databases of PubMed, PEDro Database, CINAHL Complete, Cochrane Library, EBSCO (Medline) between September 10 to October 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Rehn B. also identified in a systematic review in 2008 that eight of the nine articles in the study showed positive effects of whole body vibration exercise on bone density in the lower limbs and pelvis in postmenopausal women [32]. A systematic review of literature was also made by Baloy R.K. in 2021, where the identified studies presented substantial evidence supporting the use of WBV in increasing bone mineral density [33].…”
Section: Ta B Lmentioning
confidence: 99%
“…Rehn B. also identified in a systematic review in 2008 that eight of the nine articles in the study showed positive effects of whole body vibration exercise on bone density in the lower limbs and pelvis in postmenopausal women [32]. A systematic review of literature was also made by Baloy R.K. in 2021, where the identified studies presented substantial evidence supporting the use of WBV in increasing bone mineral density [33].…”
Section: Ta B Lmentioning
confidence: 99%